Reverberations of Nazi violence in Germany and beyond: disturbing pasts - Bird, Stephanie; Fulbrook, Mary; Wagner, Julia; Wienand, Christiane (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2016)
"Reverberations of Nazi Violence in Germany and Beyond explores the complex and diverse reverberations of the Second World War after 1945. It focuses on the legacies that National Socialist violence and genocide perpetrated in Europe continue to have in German-speaking countries and communities, as well as among those directly affected by occupation, terror and mass murder. Furthermore it explores how those legacies are in turn shaped by the present.The volume also considers conflicting, unexpected and often dissonant interpretations and representations of these events, made by those who were the witnesses, victims and perpetrators at the time and also by different communities in the generations that followed. The contributions, from a range of disciplinary perspectives, enrich our understanding of the complexity of the ways in which a disturbing past continues to disrupt the present and how the past is in turn disturbed and instrumentalized by a later present"--
Keywords: Europe -- Social conditions -- 20th century; Aufsatzsammlung; Vergangenheitsbewältigung; Kollektives Gedächtnis; Judenvernichtung; Nationalsozialistisches Verbrechen; Geschichte; Europa